2016
DOI: 10.18203/2349-3933.ijam20161084
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, morbidity and mortality among swine flu (H1N1) infected patients: 2015 Gwalior, Madhya Pradesh pandemic, India

Abstract: Background: Influenza is known to cause annual seasonal epidemics in Asian subcontinent. Our study assessed the clinical profile, factors influencing the response, prognosis and outcome in H1N1 positive patients during FebruaryMarch 2015. We aimed to understand the epidemiology and patterns of the disease so that the high risks groups could be identified. Methods: Medical records of the patients who were admitted during Feb-March 2015, as a suspected case to the swine flu ward of J A Hospital and G R Medical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…In our study, the symptoms on presentation in descending order were cough (100%), followed by throat pain (96.9%), common cold (93.85%), fever (93.85%), breathlessness (83.1%), headache (52%), chest pain (49.2%), sputum production (46.2%), vomiting (24.6%), and hemoptysis (7.7%), whereas in the study by Dhawale et al ., cough (97.72%) and fever (77.27%) were the most common presenting symptoms followed by breathlessness in 29.54% patients,[6] whereas in other study of 2011 conducted in New Delhi, fever (100%), cough (87.5%), sore throat (43.7%), and breathlessness (87.5%) were found to be the most common symptoms in Influenza A H1N1. [9] In the study by Srinivasa et al .,[10] the commonest symptoms identified were cough (100%), fever (90%), sore throat (25%), and difficulties/shortness of breath (50%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, the symptoms on presentation in descending order were cough (100%), followed by throat pain (96.9%), common cold (93.85%), fever (93.85%), breathlessness (83.1%), headache (52%), chest pain (49.2%), sputum production (46.2%), vomiting (24.6%), and hemoptysis (7.7%), whereas in the study by Dhawale et al ., cough (97.72%) and fever (77.27%) were the most common presenting symptoms followed by breathlessness in 29.54% patients,[6] whereas in other study of 2011 conducted in New Delhi, fever (100%), cough (87.5%), sore throat (43.7%), and breathlessness (87.5%) were found to be the most common symptoms in Influenza A H1N1. [9] In the study by Srinivasa et al .,[10] the commonest symptoms identified were cough (100%), fever (90%), sore throat (25%), and difficulties/shortness of breath (50%).…”
Section: Discussionmentioning
confidence: 98%
“…In another study on epidemic of swine flu of 2015 by Dhawale et al ., average age was found <50 years, whereas in our study, it was more than 50 years. [6]…”
Section: Discussionmentioning
confidence: 99%
“…3 Influenza cases infected by swine origin influenza A (H1N1) virus, was also reported from West Bengal from the month of February to March 2015 at Beliaghata ID and BG Hospital, a tertiary care hospital in Kolkata, West Bengal, India. 6 During the last resurgence in 2015, this hospital was acted as a referral center for H1N1 infected persons. H1N1 cases were confirmed by real time reverse transcriptase polymerase chain reaction (RT-PCR) on throat swab.…”
Section: Introductionmentioning
confidence: 99%
“…We found significant number of the cases of swine flu (74.7%) presented with symptoms suggestive of cardiovascular involvement (72.2% breathlessness, 27.8% chest pain, 16.5% palpitation, 10.1% presyncope, 7.6% syncope and 5.1% giddiness) at the time of hospitalization. We did not find any study evaluating cardiovascular symptoms at the time of presentation in cases of swine flu although previous study on clinical profile has shown breathlessness in 29.54% to 83.1% cases, chest pain in 13.3%-49.2% and syncope in 6.7% [16][17][18][19]. Thus our study suggests that evaluation for sign and symptoms of cardiovascular symptoms should be done at the time of presentation as they are often overlooked because of focus on respiratory symptoms like rhinorrhea, cold symptoms, throat pain and cough and patients also often ignore symptoms related to the cardiovascular system.…”
Section: Discussionmentioning
confidence: 82%
“…A total of 13 cases (16.4%) were having underlying one or more PCVD. Previous studies has also reported underlying cardiovascular disease in 4.4% to 7.89% [1,[17][18][19]. Mean age of subjects with PCVD was 63.38 ± 9.07 years as compared to 47.14 ± 17.8 without PCVD.…”
Section: Pre-existing Cardiovascular Disease and Clinical Course Of Swine Flu (Table 6)mentioning
confidence: 80%